How do older and young adults start searching for information? Impact of age, domain knowledge and problem complexity on the different steps of information searching. (July 2017) - Sanchiz, M.; Chevalier, A.; Amadieu, F.
Abstract: The present study addressed the age-related differences in query production and information searching performance when interacting with a search engine. To this end, 20 older adults and 20 young ones performed 12 information search problems of varying complexity in two knowledge domains (health and fantastic movies). Participants had simple (useful keywords provided and answer directly accessible in Google), inferential (inferences to produce useful keywords required) and multicriteria problems (information gathering and navigation required). Results showed that older adults produced their first query with more keywords extracted from the search problem statements and spent more time on the search engine pages than young ones. In the fantastic movies, older adults struggled more than young ones and had difficulties reformulating their queries (i.e. fewer new keywords produced, more statement provided keywords). Older adults especially struggled at the beginning of the search (more time spent on the first search engine result page than young ones and they produced less elaborate initial query). In contrast, in the health domain, higher prior knowledge helped older users reformulate queries that were more elaborated (i.e.no age-related differences on the number of new keywords) and improved the processing of the first search engine page consulted. Highlights: Role of age and domain knowledge on querying and search engine processing. Impact of search strategies early in the task and overall. Older adults' prior knowledge improved querying and the first stage of the search.